An approach for liver cancer detection from histopathology images using hybrid pre-trained models - Nuthanakanti Bhaskar; Jangala Sasi Kiran; Suma Satyanarayan; Gaddam Divya; Kotagiri Srujan Raju; Murali Kanthi; Raj Kumar Patra (Universitas Ahmad Dahlan, 2024)
Histopathological image analysis (HIA) plays an essential role in detecting cancer cell development, but it is time-consuming, prone to inaccuracy, and dependent on pathologist competence. This paper proposes an automated HIA that uses deep learning to improve accuracy and efficiency in liver cancer cell growth. The model uses whole slide image (WSI) input, open computer vision (OpenCV) libraries for image preprocessing, ResNet50 for patch-level feature extraction, and multiple instances learning for image-level classification. The suggested approach accurately distinguishes liver histopathological pictures as cancerous or non-cancerous. Assisting in the early detection of liver cancer cell development with potential invasion or spread.